한옥 설계의 최근 경향 연구 - 최근 10년간 건축전문 잡지에 게재된 신축 한옥을 대상으로 - 이주옥; 한필원; Lee Ju-Ock; Han Pil-Won (건축역사연구, 2012)
The objective of this study is to find out the recent trends of hanok design based on 58 hanoks appeared in architecture magazines in the last 10 years. The cases are analyzed in terms of location, size, building form, spatial organization, material, roof form, and the ceiling form of living room. The consequences of this study is as follows; Most of the recent hanoks are built in rural area (91.4%), which shows the hanok is not accepted as an urban house type. Hanoks tend to be built in 2 stories whose 2nd floor is smaller than the 1st floor. (34.5%) The preferred size is total floor area of 99.2 ~ 165.2㎡ (62.0%), 3 rooms (46.6%) with a traditional ondol room (60.3%). The buildings with ㄱ-shape (43.1%) and linear-shape (27.6%) are preferred, and the compact plan type similar with apartment house appears (13.8%). In the roof design that greatly influences the appearance of building, the traditional design factors such as half-hipped roof (55.2%), double eaves (27.6%), and eaves curve tend to be sustained. In terms of spatial organization, most of recent hanoks have double-layed plan (74.2%). The living room mostly has separately defined space. (82.8%) The indoor and outdoor tend to be connected by a narrow wooden veranda (39.7%), while some cases don't have any wooden floor space (48.3%). The entrance is adopted as an important spatial element in front part of building (75.9%), and it influences the appearance of building. The living room, the counterpart of the wooden floor hall in traditional hanok, and kitchen tend to be interiorized. In terms of material, the cement roof tile and red clay brick are preferred. Consequently, the walls of recent hanoks have the image of brick structure rather than the wooden frame structure of traditonal hanok.